2022
DOI: 10.14309/01.ajg.0000859008.65286.70
|View full text |Cite
|
Sign up to set email alerts
|

S592 Outcomes and Complications of Radiologic Gastrostomy vs Percutaneous Endoscopic Gastrostomy for Enteral Feeding - An Updated Systematic Review and Meta-Analysis

Abstract: Introduction: Percutaneous endoscopic gastrostomy (PEG) and percutaneous radiological gastrostomy (PRG) are commonly utilized to establish access to enteral nutrition. However, data comparing the outcomes of PEG vs. PRG are conflicting. Our aim was to conduct an updated systemic review and meta-analysis comparing PRG and PEG outcomes. Methods: A systematic review was conducted using Medline, Embase, and Cochrane library databases until December 21, 2021. Primary outcomes included 30-day mortality, tube leakage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Tube dislodgement after percutaneous gastrostomy can be caused by various factors. Some studies suggest that the rate of tube dislodgement is higher with the PRG approach [4]. However, this study found that the overall risk of dislodgement was lower than that reported by Vidhya [21], with similar risk between the rectus abdominis and intercostal regions.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Tube dislodgement after percutaneous gastrostomy can be caused by various factors. Some studies suggest that the rate of tube dislodgement is higher with the PRG approach [4]. However, this study found that the overall risk of dislodgement was lower than that reported by Vidhya [21], with similar risk between the rectus abdominis and intercostal regions.…”
Section: Discussioncontrasting
confidence: 75%
“…Currently available research primarily compares the clinical outcomes of PRG and PEG. The success rates of these two methods are comparable; however, higher rates of tube leakage and tube dislodgement have been noted after PRG [4]. There is no signi cant difference between the two procedures in terms of the rate of bleeding or infection around the stoma, but PRG is associated with a higher rate of adverse events such as colon perforation and peritonitis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…13 However, PRG tube diameters are thinner than PEG tubes, and they are secured using a balloon retention system, increasing the risk of tube obstruction and tube dislodgement. 18 Additionally, PRG requires a dedicated fluoroscopy suite, which may not be readily available. 13 Previous systematic reviews and meta-analyses comparing the efficacy and safety of PRG vs PEG predominantly relied on observational studies and yielded conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…13 Previous systematic reviews and meta-analyses comparing the efficacy and safety of PRG vs PEG predominantly relied on observational studies and yielded conflicting results. [17][18][19][20][21] Some studies found that PRG leads to a higher rate of 1-month mortality 18,20 ; major adverse events (AEs), such as peritonitis and colon perforation 18,20 ; and tube problems. [17][18][19] On the other hand, one meta-analysis showed higher technical success with PRG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation